Implementing the Hollow Sprint Training Method to Increase 100 Meter Running Speed - Agus Sutriawan; Muhammad Akbar Syafruddin (Journal Physical Health Recreation (JPHR), 2025)
This research method uses a quantitative approach with a quasi-experimental design in the form of a one-group pretest and posttest design. The sample used was 40 students of the Faculty of Sport and Health Sciences (FIKK) of Makassar State University (UNM) who participated in this study. The research procedure began with the implementation of a pretest, namely measuring the 100-meter running speed of each participant using a stopwatch as the main measurement instrument. The pretest aims to determine the initial running speed ability before being given the Hollow Sprint training treatment. After that, all participants participated in the Hollow Sprint training program carried out for a certain period, for example 12 meetings or according to the research needs. Based on the results of the paired sample t-test on the data on the 100-meter running speed ability of students of the PJKR FIKK UNM Study Program, it was obtained that the average value (mean) of the pre-test result was 15.42 seconds, while the average post-test result was 13.47 seconds. There was an average difference (mean difference) of 1.96 seconds, which indicates an increase in running speed ability after students participated in the training program or treatment given. Based on the data analysis, it can be concluded that there was a significant increase in the 100-meter sprint speed of students at the Physical Education and Sports Faculty (FIKK) of Universitas Negeri Makassar (UNM) after being given the Hollow Sprint training program.